ISPC Commentary on the Revised Proposal for CRP1.1 - February 2013 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
ISPC Commentary on the revised proposal Integrated agricultural production systems for improved food security and livelihoods in dry areas (CRP1.1 Drylands Systems Program) (Version of 28 January 2013).